(3GdeSc GdYGWQ aj Md RjL GHf GdTGWQs - (3jhSa Hf CMeO Hf GdfGHdSj GdTGaYjs
(3ChdgG (B:s
(3MeOkG def QaY GdSeGA hHfGgG CeG HYO ajbhd jhSa Hf CMeO Hf CHQGgje GdfGHdSi deG hbaJ Ydi WGFaI ef CRjGL GdJbGhje GdJi ef GdYUQ GdbOje CYde YdeGA GdeJbOejf ai gPg GdUfGYI s
(3BNQgG (B:s
(3hgPG BNQ eG JjSQ ef hGQOGJ GdaJM GdQHGfi hGdaJM GdUeOGfi hYdi Gddg bUO GdSHjd hgh MSHfG hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdMQha h GdChaGbs